A comparison of misoprostol vaginal insert and misoprostol vaginal tablets for induction of labor in nulliparous women: a retrospective cohort study - Kjersti Engen Marsdal; Ingvil Krarup Sørbye; Lise C. Gaudernack; Mirjam Lukasse (BMC, 2018)
Abstract Background Since Misoprostol Vaginal Insert (MVI - Misodel ®) was approved for labor induction in Europe in 2013, to date, no study has been published comparing MVI to Misoprostol vaginal tablets (MVT). The aim of this study, performed as part of a quality improvement project, was to compare the efficacy and safety of 200 μg MVI versus 25 μg MVT for labor induction in nulliparous women. Methods This retrospective cohort study included 171 nulliparous singleton term deliveries induced with MVI (n = 85) versus MVT (n = 86) at Oslo University Hospital Rikshospitalet, Norway, from November 2014 to December 2015. Primary outcomes were time from drug administration to delivery in hours and minutes and the rate of cesarean section (CS). Results were adjusted for Bishop Score and pre-induction with balloon catheter. Results Median time from drug administration to delivery was shorter in the MVI group compared to the MVT group (15 h 43 min versus 19 h 37 min, p = 0.011). Adjusted for confounding factors, mean difference was 6 h 3 min (p = 0.002). The risk of CS was 67% lower in the MVI group compared to the MVT group (11.8% versus 23.3%, OR = 0.33; adjusted 95% CI 0.13-0.81). Adverse neonatal outcomes did not differ between the groups. Conclusions In a setting of routine obstetric care, MVI seems to be a more efficient labor induction agent than MVT, and with a lower CS rate and no increase in adverse infant outcomes.